Proposal for Managing Eco-efficient Operations Plant Dedicated to Waste Handling at Costa Rican Institute of Electricity - Chinchilla, Annie (2015)
In the present study, different eco-efficient specifications were established considered by Ingeniería y Construcciónor IC (Engineering and Construction), a business of the Costa Rican Institute of Electricity (ICE, in Spanish), at the time of developing an operational plant devoted to the handling of waste, in order to make rational use of resources and generate the lowest environmental impact. Initially a general diagnosis was conducted to learn about the current process of waste management in IC, as well as the identification and assessment of its aspects and environmental impacts. An ecoefficiency proposal program was subsequently prepared to be implemented once the ordinary, special and hazardous waste plant is operating. As part of this investigation, eco-efficient measures and technologies were also identified; this can be adopted by IC or any organization to improve its waste management. Finally, it is necessary that the Eco-efficient Management Program (PGE, in Spanish) is organized, planned and systematized over time; in addition, the need to have an Ecoefficiency Management Committee arises, which will allow to implement it and measure it through a series of indicators.